Enhancing Construction Safety and Health through IoT and Wearable Devices: A Systematic Review - Darwis Baso (JACEE (Journal of Advanced Civil and Environmental Engineering), 2025)
The construction industry faces some of the highest occupational safety and health (OSH) risks, driven by hazardous behaviors, unsafe conditions, and limited adoption of technology and training. This study employs a systematic literature review (SLR) of recent publications to evaluate the trends, benefits, and challenges of applying Internet of Things (IoT) and wearable devices in construction OSH management. The findings indicate that technologies such as smart helmets, sensor vests, and biometric wristbands enable real-time monitoring, early risk detection, and predictive safety management, reducing reliance on traditional inspection methods. Furthermore, the integration of IoT with Artificial Intelligence (AI), Big Data Analytics, Building Information Modeling (BIM), and Industry 5.0 principles enhances predictive capacity, infrastructure resilience, efficiency, and sustainability of construction projects. Despite these benefits, barriers including data privacy concerns, high implementation costs, interoperability issues, and shortages of skilled personnel remain, especially in developing countries such as Indonesia. Overall, IoT and wearable technologies demonstrate significant potential to transform OSH practices in the construction sector by improving safety, productivity, and sustainability. However, their broader adoption requires comprehensive strategies, including worker training, strong data protection policies, regulatory support, and participatory approaches to ensure effective and sustainable implementation.